Functional identification of purine permeases reveals their roles in caffeine transport in tea plants (Camellia sinensis) - Zhang, Yazhen; Wei, Kang; Guo, Lingling; Lei, Yuping; Cheng, Hao; Chen, Changsong; Wang, Liyuan (Frontiers in Plant Science, 2022)
Caffeine is a characteristic secondary metabolite in tea plants. It confers the unique flavor and excitation effect of tea as a popular beverage. Currently, the pathway of caffeine biosynthesis has been generally established, but the mechanism of caffeine transport remains unclear in tea plants. Here, eight purine permeases (PUPs) members were identified in tea plants. The diverse expression patterns of these CsPUPs in different tissues suggested their broad roles in caffeine metabolism. Correlation analysis showed that the transcripts of three CsPUPs (CsPUP1, CsPUP3.1 and CsPUP10.1) were all significantly negatively correlated with caffeine content in tea leaves of eight strains and six cultivars. Furthermore, subcellular localization revealed that all three CsPUPs were not only located in plasma membrane, but also widely distributed as circular organelles in cells. Functional complementation assays in yeast showed that all three CsPUPs could partly or completely rescue the defective function in caffeine transport of fcy2 mutant. Among them, transgenic yeast of CsPUP10.1 exhibited the strongest capacity of caffeine transport. Consistent phenotype and caffeine transport function were further identified in the CsPUP10.1-over-expression Arabidopsis lines. Taken together, it suggested that CsPUPs were involved in caffeine transport in tea plants. Potential roles of CsPUPs in the intracellular transport of caffeine among different subcellular organelles were proposed. This study provides a theoretical basis for further research on PUP genes and new insights for caffeine metabolism in tea plants.